PELATIHAN KESIAPSIAGAAN MENGHADAPI BENCANA UNTUK ANAK USIA DINI - Damayanti, S.; Purnawati, K.W.; Dewi, N.M.A.; Wedayanti, N.P.L.; Sulatri, N.L.P.A.; Lestari, N.P.C.; Putra, I.G.G.P.A. (Buletin Udayana Mengabdi; Vol 22 No 2 (2023): Buletin Udayana MengabdiDO - 10.24843/BUM.2023.v22.i02.p01, 2023)
Batubulan Village, Sukawati District, Gianyar Regency, is one of the areas in Bali that is prone to earthquake and tsunami disasters. This community service in the form of disaster preparedness training given to teachers and children of Bali Kumara Kindergarten aims to increase knowledge and skills in dealing with natural disasters, especially earthquakes and tsunamis. This training combined three disaster education methods, which included the kamishibai method or storytelling "Sahabat Naga Boga and Besuki", disaster mitigation socialization and disaster simulation training conducted by professional speakers and facilitators from the Bali Provincial Disaster Management Agency (BPBD). Through this disaster preparedness training, the knowledge of teachers and students about disasters has increased. In addition, this training formed the character of disaster responsiveness in students because children can face disasters in appropriate ways. It is hoped that this service will become a continuing program to ensure that the children have a good knowledge of disaster mitigation. Keywords: earthquake, tsunami, storytelling, disaster, mitigation